A Family of Viscosity Splitting Scheme for the Navier-Stokes Equations (Journal of Computational Mathematics, 2018)
In the paper, a family of viscosity splitting method is introduced for solving the initial boundary value problems of Navier-Stokes equation. Some stability and convergence estimates of the method are proved.